Working with Images: Understanding—Use—Instrumentalization (KULT_online, 2011)
With her monograph Sozialtheorie des Bildes (Social Theory of the Image), sociologist Roswitha Breckner presents a work in which theory and philosophy of the image becomes the basis for a larger understanding of pictorial representation. She aims to spur a discussion about what pictures have to do with reality. She shows the function and procedure of the method of a segment analysis. The whole theoretical part is mainly based on the theory of symbol by Susanne Langer. With that choice, she realizes not only a theoretical basis, but also a change of perspective, which allows for looking at pictures without thinking of the media of their representation.